Human Interaction with Artificial Intelligence - Michal KOLOMAZNIK; Michal SLAMA (Communications of International Proceedings, 2022)
Artificial Intelligence is penetrating our everyday lives more often, an evolutionary step to increase human productivity. Socially oriented human beings have been shown to achieve greater work efficiency when their AI counterparts respond in ways that better mimic human behavior. Paper is a review exploring in more detail the potential applications of AI, with a particular focus on human-computer interaction. Based on a closer examination of the existing literature, passages relevant to further AI design and its emulation of social interactions, were selected. Particularly those which create a sense of trust, empathy, and shared understanding leading people to respond as they do to another human being The presented text provides a basic overview of what aspects of communication make thinking computer systems interaction human-like enough that end-users feel empowered and motivated to see AI as a partner rather than a machine.
Keywords: Autonomous technology; human–robot interaction; artificial intelligence as social actors; perception of AI.